1996
DOI: 10.1037/0022-3514.70.3.461
|View full text |Cite
|
Sign up to set email alerts
|

Approach and avoidance achievement goals and intrinsic motivation: A mediational analysis.

Abstract: Most contemporary achievement goal conceptualizations consist of a performance goal versus mastery goal dichotomy. The present research offers an alternative framework by partitioning the performance goal orientation into independent approach and avoidance motivational orientations. Two experiments investigated the predictive utility of the proposed approach-avoidance achievement goal conceptualization in the intrinsic motivation domain. Results from both experiments supported the proposed framework; only perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
1,540
13
131

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,929 publications
(1,743 citation statements)
references
References 67 publications
(75 reference statements)
59
1,540
13
131
Order By: Relevance
“…In contrast, when assigned either mastery or performance-approach goals, Barron and Harackiewicz replicated the pattern found previously by Harackiewicz and Elliot. Although previous research provides some suggestions for how achievement motivation may moderate the impact of performanceapproach and mastery goals on interest, much less research has been done examining performance-avoidance goals and interest. Elliot and Harackiewicz (1996) found that assigned performanceavoidance goals were associated with lower interest as compared with assigned performance-approach, mastery, or performanceneutral goals, but these authors did not assess individual differences in achievement motivation. One possibility, therefore, is that when assigned performance-avoidance goals under conditions of stereotype threat, both individuals higher and lower in achievement motivation will experience lower interest, with the key difference being that individuals higher in achievement motivation would be more likely to spontaneously adopt performanceavoidance goals in those situations.…”
Section: Role Of Achievement Motivationmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, when assigned either mastery or performance-approach goals, Barron and Harackiewicz replicated the pattern found previously by Harackiewicz and Elliot. Although previous research provides some suggestions for how achievement motivation may moderate the impact of performanceapproach and mastery goals on interest, much less research has been done examining performance-avoidance goals and interest. Elliot and Harackiewicz (1996) found that assigned performanceavoidance goals were associated with lower interest as compared with assigned performance-approach, mastery, or performanceneutral goals, but these authors did not assess individual differences in achievement motivation. One possibility, therefore, is that when assigned performance-avoidance goals under conditions of stereotype threat, both individuals higher and lower in achievement motivation will experience lower interest, with the key difference being that individuals higher in achievement motivation would be more likely to spontaneously adopt performanceavoidance goals in those situations.…”
Section: Role Of Achievement Motivationmentioning
confidence: 97%
“…Performance-avoidance goals are defined as wanting to avoid demonstrating incompetence (e.g., Elliot & Church, 1997;Wolters, 2004;e.g., I want to avoid failing the computer science task) and often have negative effects on learning and motivation (e.g., Elliot & Harackiewicz, 1996;Elliot et al, 2005). In contrast, effects of performance-approach goals on performance and motivation appear to depend both on the context and on individual differences.…”
Section: The Step Modelmentioning
confidence: 99%
“…In contexts where a psychological MS# 2003 climate for performance emerges, ongoing assessments of performance are designed to motivate group members to outperform one another, whereas in contexts in which individuals view avoiding failure as valued, performance is consistently monitored to detect errors and minimize their consequences. Experimental research shows that these subtle nuances in perception effectively cue the expected form of state performance orientation (Elliot & Harackiewicz, 1996;Harackiewicz & Elliot, 1993).…”
Section: Relation Between Psychological Climate and Group Member Statmentioning
confidence: 99%
“…This is true of rewards in general (Deci, Koestner, & Ryan, 1999), but several studies demonstrate that this is particularly true for goals themselves (Elliot & Harackiewicz, 1996;Rawsthorne & Elliot, 1999). …”
Section: When Goals Harm Motivation Itselfmentioning
confidence: 99%